2020
DOI: 10.1055/a-1186-1316
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Stabilization Time for Ultra-short Heart Rate Variability Measurements in Professional Soccer

Abstract: The main aims of this study were: 1) to compare 1-minute RMSSD measurements using different stabilization times between them and also with the criterion; and 2) to determine the agreement between every 1-minute RMSSD measurement with the criterion in professional soccer players. Seven hundred eighteen HRV measurements from professional soccer players were taken. HRV was calculated from 5 to 10 minutes (criterion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A limited number of studies (n = 8), included in this review, employed a prestabilization period before sampling (Supplementary Material S2). In contrast to previous findings [61,65], one study included in this review indicated that a minimum of 1 min of prestabilization was necessary for resting RMSSD when supine UST measurements were conducted on elite male soccer players [46]. Additionally, when at least 1 min of prestabilization was implemented during UST measurements, the results for different measurement durations were comparable to those for the criterion period [46].…”
Section: Hrv Use Implementation and Measurement Protocolcontrasting
confidence: 75%
See 1 more Smart Citation
“…A limited number of studies (n = 8), included in this review, employed a prestabilization period before sampling (Supplementary Material S2). In contrast to previous findings [61,65], one study included in this review indicated that a minimum of 1 min of prestabilization was necessary for resting RMSSD when supine UST measurements were conducted on elite male soccer players [46]. Additionally, when at least 1 min of prestabilization was implemented during UST measurements, the results for different measurement durations were comparable to those for the criterion period [46].…”
Section: Hrv Use Implementation and Measurement Protocolcontrasting
confidence: 75%
“…The study quality of HRV methodology was evaluated with a slightly modified version [36] of the STARD HRV [35]. The average score of the STARD HRV was 14.6/25 and ranged from 8 [58] to 18 [46, 51, 54]. Nearly all studies provided enough information about the device setup and metrics used.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, previous studies showed that variables such as RMSSD or the stress index are biomarkers of internal load, and therefore are sensitive enough to detect fatigue [49,50]. This is extremely useful since the player cannot voluntarily alter HRV results, unlike subjective scales such as wellness or stress questionnaires [51]. However, different protocols of HRV monitoring during sports seasons can be found in the scientific literature [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…While HRV traditionally had to be measured under well-controlled conditions (e.g., in a rested state, seated or supine position, controlled breathing and for minimally 5 min) (Malik et al 1996 ), more recently, several researchers have started using ultra-short LnRMSSD measurements (as short as 30 s) after submaximal exercise, to monitor training status in athletes (Munoz et al 2015 ; Krejci et al 2018 ; Forner-Llacer et al 2020 ). Although the findings of these studies are promising and the reduced time frame will assist with the practical applicability, LnRMSSD in these studies was still measured in a rested state to assure stability in potential confounding factors, such as heart and breathing rate during the measurement.…”
Section: Introductionmentioning
confidence: 99%